Musculoskeletal Atrophy in an Experimental Model of Knee Osteoarthritis: The Effects of Exercise Training and Low-Level Laser Therapy. (August 2015) - Assis, Livia; Almeida, Thais; Milares, Luiz Paulo; dos Passos, Nayara; Araújo, Bruna; Bublitz, Caroline; Veronez, Suellen; Renno, Ana Claudia Muniz
ABSTRACT: Objective: The aim of this study was to evaluate the effects of an exercise training protocol and low-level laser therapy (and the association of both treatments) on musculoskeletal atrophy using an experimental model of knee osteoarthritis (OA). Design: Fifty male Wistar rats were randomly divided into five groups: control group, knee OA control group, OA plus exercise training group, OA plus low-level laser therapy group, and OA plus exercise training associated with low-level laser therapy group. The exercise training and the laser irradiation started 4 wks after the surgery, 3 days per week for 8 wks. The exercise was performed at a speed of 16 m/min, 3 days per week, 50 mins per day, for 8 wks. Laser irradiation was applied at two points of the left knee joint (medial and lateral), for 24 sessions. Results: The results showed that both trained groups (irradiated or not) presented a significant increase in the muscle cross-sectional area and a decrease in muscle fiber density compared with the knee OA control group. Moreover, both trained and laser-irradiated groups demonstrated decreased muscle-specific ring-finger protein 1 and atrogin-1 immunoexpression. Conclusions: These results suggest that exercise training and low-level laser therapy were effective in preventing musculoskeletal alterations related to atrophy caused by the degenerative process induced by knee OA.